RANCANG BANGUN OPEN ACCESS JOURNAL MENGGUNAKAN METODE OBJECT ORIENTED DENGAN PENDEKATAN UML-BASED WEB ENGINEERING - Ade Sutedi; Cepy Slamet; Dhami Johar Damiri (Institut Teknologi Garut, 2015)
Open Access (OA) literature is digital, online, free of charge, and free of copyright and licensing restrictions. Open Access Journal is one of the Open Access (OA Gold) used in the process of publication of journals through the Internet. Open Access Journal allows users to maximize the process of publishing that are peer-reviewed. Peer-review process conducted by the Authors, Editors, and Reviewers journals become a registered user on the Open Access Journal. Open Access models are used to simplify the process of publication of journals that are closed and takes a long time and reduce storage space for publications. With Open Access, users such as author, editor, or reviewer can make the process of writing and editing the journal on the media that can be accessed anywhere and anytime. To model of Open Access use web applications development approach is UML - based Web Engineering (UWE). UWE UML provides a graphical notation that depicts the elements of the model, which supports the generation method of semi - automatic, and the process of web development life cycle.